EFFECTS OF HEAVY METALS ON GROWTH AND NODULATION OF RHIZOBIUM SP. IN VIGNA RADIATE (L.) WILCZEK - Shubhranshee Sanshlishta Sahu , Pratyasha Mohanty , Gyanranjan Mahalik (International Journal of Modern Agriculture, 2020)
Nowadays heavy metal contamination is widespread in the lithosphere as well as in the hydrosphere. Huge territories of land have been debased with substantial metals because of the utilization of pesticides, manures, and fertilizer squanders, and furthermore because of overwhelming metal discharge from purifying industries and metalliferous mines. To avoid the contamination of heavy metals from polluted water and soil phytoremediation process is used, which includes plants like some floating hydrophytes and legumes. Rhizobium is a genus of gram-negative soil bacteria that fix nitrogen by symbiotic association with leguminous plants and usually form root nodules. Treatment with CdCl2 and NiCl2 had the most harmful impact on the growth of Rhizobium. Nodulation boundaries e.g. “number of plants nodulated, number of nodules per plant, number of nodules per gram fresh weight of the roots, nodule dry weight per plant, and weight of the nodule were inhibited, the hindrance being fixation subordinate”. The impact was indistinguishable in all the overwhelming metal salts tried. Inhibitory consequences for nodulation have been evaluated because of the restraint of the development of Rhizobium by the impact of the overwhelming metal salts. These Rhizobia can be utilized as inoculants for crop legumes under ominous ecological states of agrobiological systems or as of late recovered desert